High-throughput rapid amplicon sequencing for multilocus sequence typing of Mycoplasma ovipneumoniae from archived clinical DNA samples - Framst, Isaac; Wolking, Rebecca M.; Schonfeld, Justin; Ricker, Nicole; Beeler-Marfisi, Janet; Chalmers, Gabhan; Kamath, Pauline L.; Maboni, Grazieli (Frontiers in Veterinary Science, 2024)
Spillover events of Mycoplasma ovipneumoniae have devastating effects on wild sheep populations. Multilocus sequence typing (MLST) is used to monitor spillover events and the spread of M. ovipneumoniae between sheep populations. Most work involving M. ovipneumoniae typing has used Sanger sequencing. However, this technology is time-consuming, expensive, and is not well suited to efficient batch sample processing. Our study aimed to develop and validate an MLST workflow for typing of M. ovipneumoniae using Nanopore Rapid Barcoding sequencing and multiplex PCR. We compare the workflow with Nanopore Native Barcoding library preparation and Illumina MiSeq amplicon protocols to determine the most accurate and cost-effective method for sequencing multiplex amplicons. A multiplex PCR was optimized for four housekeeping genes of M. ovipneumoniae using archived DNA samples (N = 68) from nasal swabs. Sequences recovered from Nanopore Rapid Barcoding correctly identified all MLST types with the shortest total workflow time and lowest cost per sample when compared to Nanopore Native Barcoding and Illumina MiSeq methods. Our proposed workflow is a convenient and effective method for strain typing of M. ovipneumoniae and could be applied to other bacterial MLST schemes. The workflow is suitable for diagnostic settings where reduced hands-on time, cost, and multiplexing capabilities are important.